2018
DOI: 10.3390/ijerph15102131
|View full text |Cite
|
Sign up to set email alerts
|

Do Occupational and Patient Safety Culture in Hospitals Share Predictors in the Field of Psychosocial Working Conditions? Findings from a Cross-Sectional Study in German University Hospitals

Abstract: Background: In the healthcare sector, a comprehensive safety culture includes both patient care-related and occupational aspects. In recent years, healthcare studies have demonstrated diverse relationships between aspects of psychosocial working conditions, occupational, and patient safety culture. The aim of this study was to consider and test relevant predictors for staff’s perceptions of occupational and patient safety cultures in hospitals and whether there are shared predictors. From two German university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…Furthermore, as sub‐group analyses could not be justified in this study due to the small sample size, future studies should explore whether these relationships differ across occupations. For example, Wagner et al () found that hospital physicians and nurses differed in their perceptions of patient safety culture, with physicians rating the culture more positively than nurses did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as sub‐group analyses could not be justified in this study due to the small sample size, future studies should explore whether these relationships differ across occupations. For example, Wagner et al () found that hospital physicians and nurses differed in their perceptions of patient safety culture, with physicians rating the culture more positively than nurses did.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies emphasize the role of leaders in building a safety culture (Merrill, ; Wagner et al, ; Wong, Cummings, & Ducharme, ). McFadden, Henagan, and Gowen () found that transformational leadership was directly related to patient safety culture and indirectly related to patient safety outcomes through culture and patient safety initiatives, such as education and training of employees and system redesign.…”
Section: Introductionmentioning
confidence: 99%
“…The WorkSafeMed study ("Working conditions, safety culture and patient safety in hospitalswhat predicts the safety of the medication process") was a crosssectional, multicenter, mixed-methods project conducted between 2014 and 2017 [15][16][17][18]. The study included a staff survey using a standardized paper-based questionnaire to assess psychosocial working conditions (G-COPSOQ II), patient and occupational safety cultures [15,16], a chart review to evaluate the quality of the medication process [17] and the explorative correlation analysis of questionnaire and routine data to depict workload and quality of care [18].…”
Section: Design and Settingmentioning
confidence: 99%
“…The paper-based questionnaire for the staff survey in the WorkSafeMed study used common and validated instruments [15,16]. To assess psychosocial working conditions, we employed 17 scales of the G-COPSOQ II [9,19].…”
Section: Questionnairementioning
confidence: 99%
“…However, in many studies, safety culture refers only to patient safety culture [6,7], and occupational safety culture of employees is not addressed. In some studies, occupational safety culture was considered in addition to patient safety culture [8][9][10][11][12][13][14], but did not represent the main aspect. The role of working conditions with regard to work-related injuries in healthcare (e.g., needle stick injuries) has been widely studied [15,16].…”
Section: Workplace Characteristics and Circumstancesmentioning
confidence: 99%